EFFECT OF INSTITUTIONAL QUALITY, DIASPORA REMITTANCES AND FOREIGN DIRECT INVESTMENT ON ECONOMIC GROWTH IN WEST AFRICA MONETARY ZONE - BOLAJI , TITILOPE AJILEYE; ANYANWU, SARAH OLANREWAJU (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study examines the effect of institutional quality, diaspora remittances, and foreign direct investment on economic growth in the WAMZ region for the period from 1990 to 2022. Using the Panel Autoregressive Distributed Lagged model, the study established that institutional quality stimulates growth while diaspora remittances negatively impact growth in the long run but insignificantly spur growth in the short run. FDI emerges as a critical contributor to longrun economic growth despite its short-run negative effect. The study also finds that the economy will swiftly restore equilibrium aftershocks at a speed of adjustment of 79.5%. In addition, there is a unidirectional causality between the control of corruption and economic growth, a bidirectional causality between the economic freedom index and economic growth, and between FDI and economic growth. However, there is no causal relationship between diaspora remittance and economic growth. Based on these outcomes, the study recommends that WAMZ governments and policymakers prioritise improving and enforcing a robust legal and regulatory framework to inhibit corrupt practices, ensure transparency, and prevent market monopolies. The study also suggests encouraging diaspora investment through attractive incentives, as remittances have the potential to stimulate economic growth significantly. Lastly, governments should create a conducive environment for business operations, with a strong emphasis on transparency, as this is a crucial factor in economic growth.